Solvent-induced self-assembly of uniform lying helix alignment of the cholesteric liquid crystal phase for the flexoelectro-optic effect. Issue 5 (9th April 2018) - Bolis, S.; Tartan, C. C.; Beeckman, J.; Kockaert, P.; Elston, S. J.; Morris, S. M.
ABSTRACT: A uniform lying helix (ULH) alignment of cholesteric liquid crystals (LCs) is obtained using a solvent evaporation technique. The solvent evaporation method allows for the spontaneous formation of a virtually defect-free alignment, even in the absence of an external electric field. A small amount of solvent diffuses into the LC and changes its phase into isotropic state where the individual LC molecules are more mobile. As the solvent diffuses out of the LC and consequently evaporates, additional mobility provided by the solvent allows the molecules to reach the lowest energy configuration, dictated by the boundary conditions, the solvent evaporation direction and the elastic forces among the molecules. Compared to a shear-flow-induced alignment, the solvent-induced ULH exhibits a contrast ratio between the bright and dark states that is a factor of 4 times larger, due to the low number of defects in the structure. From measurements of the flexoelectro-optic effect, the difference between the splay and bend flexoelectric coefficients, , for the nematic LC E7 is found to be in agreement with the measured values reported in the literature (12.1 1.0 pC/m), demonstrating that the solvent self-aligning does not change the electric response of the medium, while improving its optical properties. GRAPHICAL ABSTRACT: